Effect of Harvesting Period on The Sugar Contents of Trifoliate Yam Flour - Abiodun, O. A.; Akinoso, R.; Oladapo, A. S.; Odedeji, J. O. (AFRICAN JOURNAL OF APPLIED RESEARCH, 2015)
Trifoliate yam is one of the under-exploited yam species cultivated in Nigeria. Utilization of the tuber is limited due to the hardening process which occurs few hours after harvesting. The tubers are kept in the soil after maturity until they are needed as food. Sugar concentration is one of the major parameter that affects the textural quality of food. Therefore, this work studied the effect of harvesting period on the sugar contents of trifoliate yam flour. Trifoliate yam tubers (white and yellow cultivars) were harvested at seven, eight, nine, ten and eleven months after planting. The tubers were made into flours and subjected to sugar analysis. Sucrose, fructose and glucose were the major sugars in the two trifoliate yam cultivars. Highest value (1071.65 mg/100g) of sucrose was at 9 month in the white cultivar while the highest level in the yellow cultivar was at 10 months (983.12 mg/100g). The highest total sugar level was at 11 months (1377.49 mg/100g) in white cultivar and the least value in yellow cultivar at 7 months (1042.86 mg/100g). Total sugar levels in both cultivars increased with harvesting periods. The flour produced at different harvesting periods had variations in sugar concentration as this provides information on the usefulness of the flour for household and industrial use.